Does the wrist flexion affect on the electrophysiological studies in the healthy voluntaries? - Pinar Doruk; Mehmet Adam; Berrin Leblebici (Çukurova Üniversitesi Tıp Fakültesi Dergisi, 2011)
PURPOSE: The aim of this study is to evaluate the effects on the median nerve distal sensory latencies (dsl), first digit median vs. radial sensory latency difference, fourth digit median vs. ulnar sensory latency difference which are repeated after performing the provocative wrist flexion for about five minutes in the healhty voluntaries. MATERIALS-METHODS: In this study, 20 women, 5 men voluntaries (total 46 hands) were investigated. The median nerve dsl, the first digit median vs. radial sensory latency differences, the fourth digit median vs. ulnar sensory latency differences were recorded. After performing the provocative wrist flexion (bilaterally 90 degree) for about five minutes, above mentioned studies were repeated. RESULTS: The mean age of the voluntaries in the study was 32.8±8.4 years. Before and after provocation, the mean dsl of median nerve was 2.71±0.19 msc, and 2.73±0.17 msc, and the mean amplitude of median nerve was 35.8±21.8, and 40.2±22.2 microvolt, the mean of fourth digit median vs. ulnar sensory latency differences was 0.12±0.18 msc, and 0.15±0.19 msc, the mean of first digit median vs. radial sensory latency differences was 0.13±0.23 msc and 0.24±0.47 msc, respectively. Statistically, there were no significance between before and after the provocation at the mean value of amplitude and dsl, the median vs. radial first digit and the median vs. ulnar fourth digit sensory latency differences measurements (p>0.05). CONCLUSION: The provocative wrist flexion in the healthy voluntaries has no effect on the electrophysiological studies. [Cukurova Med J 2011; 36(1.000): 24-28]